Desempenho técnico-financeiro de sistema híbrido eólico-solar aplicado ao bombeamento de água - Arruda, Marcelo Ferreira de (2015)
This work has as main objective the installation and technical - financial evaluation of a hybrid wind - photovoltaic system applied to water pumping . In addition, a sizing methodology is proposed based on renewable sources considering low cost and available potential. The hybrid system was installed in front of the Pici Campus reservoir of the Federal Univers ity of Ceará (UFC) in Fortaleza /CE, Brazil. The hybrid system consists of 01 wind turbine of 1 kW, 04 photovoltaic modules of 87 Wp, a battery bank with 05 units of 150 Ah. The pumping system con sists of a motor - pump 0, 5 cv . Technical analysis was performed by analyzing the data (electric and non - electric) collected by sensors to a supervisory system. The results indicate that the wind resource variation for the site is higher, when compared to the solar resource, and the availability of the potential of both resources are concomitant during the daytime period, a characteristic also observed in the anal yzed period. T he generation system with battery bank, operating in either the hybrid configuration or individual, assured the supply of electricity to the pumping system during operating time . From the indicators of efficiency, it was found that the conver sion units showed divergence between estimated and measured electricity generation, and wind unit which presented greater divergence. The electricity cost of the hybrid system (wind - solar) installed with battery bank is 0.86 R$/kWh. The sizing of the generating system indicated that the hybrid configuration at the site does not fit due to the high solar potential available and the low availability of wind resources in the 1 st trimester of the year . The sizing generation system indicated that th e hybrid configuration has the lowest cost (1.52 R$/kWh) when sizing with the resources of October month . Indicating thus , that when more than one renewable source stands out , the hybrid configuration can be viable alternative